Observation of light-driven band structure via multiband high-harmonic spectroscopy - Uzan-Narovlansky, Ayelet J.; Jimenez-Galan, Alvaro; Orenstein, Gal; Silva, Rui E. F.; Arusi-Parpar, Talya; Shames, Sergei; Bruner, Barry D.; Yan, Binghai; Smirnova, Olga; Ivanov, Misha; Dudovich, Nirit (Nature Photonics, 2022)
Intense light–matter interactions have revolutionized our ability to probe and manipulate quantum systems at sub-femtosecond timescales1, opening routes to the all-optical control of electronic currents in solids at petahertz rates2–7. Such control typically requires electric-field amplitudes in the range of almost volts per angstrom, when the voltage drop across a lattice site becomes comparable to the characteristic bandgap energies. In this regime, intense light–matter interaction induces notable modifications to the electronic and optical properties8–10, dramatically modifying the crystal band structure. Yet, identifying and characterizing such modifications remain an outstanding problem. As the oscillating electric field changes within the driving field’s cycle, does the band structure follow and how can it be defined? Here we address this fundamental question, proposing all-optical spectroscopy to probe the laser-induced closing of the bandgap between adjacent conduction bands. Our work reveals the link between nonlinear light–matter interactions in strongly driven crystals and the sub-cycle modifications in their effective band structure.
CRIS-Team Scopus Importer:2023-04-20